Implementation Of The Regulation Of The Minister Of Agraria And Spatial Planning/ Head Of The National Land Agency Of The Republic Of Indonesia Number 5 Of 2020 Concerning Electronic Integrated Liability Rights Services (Study At The Blitar City Land Office) - Sunardi, Sunardi; Isnaeni, Diyan; Prisnawan, Ari (Universitas Islam Malang, 2023)
Abstract : Entering the digital era in today's technological developments, the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency, hereinafter referred to as ATR/BPN, has launched electronic land services. The electronic service in question concerns digital or electronic mortgage services. This was marked by the publication of Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 9 of 2019 concerning Electronic Integrated Mortgage Rights services, hereinafter referred to as Minister of Atr/Bpn Regulation No. 9 of 2019. And revoked and replaced with Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 5 of 2020 concerning Electronic Integrated Mortgage ServicesProblem formulation 1) How to implement the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 5 of 2020 concerning Electronically Integrated Mortgage Rights Services at the Blitar City Land Office. 2) What are the obstacles in managing mortgage rights (Ht-El) for individuals who are not financial institutions at the Blitar City Land Office. 3) What steps are taken by the Blitar City Land Agency to resolve these obstacles. The method in this research is empirical research with a sociological and legislative approach with data collection techniques using document studies, interviews.Results of research on the implementation of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 5 of 2020 concerning Electronically Integrated Mortgage Rights Services at the Blitar City Land Office. At first it didn't work well because it was a new product that had been implemented at the Blitar City Land Office, in other words it didn't work effectively. What are the Obstacles in Managing Mortgage Rights (Ht-El) for Individuals and Not Financial Institutions at the Blitar City Land Office? That the main obstacle often experienced by Htel users and administrators is the IT system on HT-el or the HT-el application which is still often problematic and lacking. human resources at ATR BPN Blitar City. What steps have been taken by the Blitar City Land Agency in resolving these obstacles, including server repairs and training for Blitar City BPN Atr officials as well as outreach to the community and PPAT. Keywords : regulations, mortgage rights, electronics.